A Critical Review of The Role of Strategic Leadership, Organizational Learning, and Organizational Culture: The Case of The Timor-Leste National Police - Arquimino Ramos; Lena Ellitan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Every Organization will strive to achieve its goals. This is the logical consequence of the establishment of the organization. Especially in today’s world development that is increasingly rapid with changes, this requires every organization including all public institutions to be able to adapt so as not to be left behind in realizing its vision, mission and goals. Moreover, it is realized that one of the things needed in achieving organizational goals is to improve organizational performance. For this reason, every organization must have the right strategy and be able to face challenges as well as be able to provide solutions to the problems they face. An organization in carrying out its plans and strategies requires strategic leadership that can drive all the potential of the organization to achieve the goals of the organization. In this case, all organizational units ranging from organizational leaders to members must cooperate and support each other, for that mutual commitment is needed in carrying out their respective functions in order to achieve common goals. Furthermore, Organizational Learning can be said to be an organization that has the ability to always improve performance continuously or continuously because its members have individual commitment and ability to learn and share knowledge at a high level. For this reason, a conducive organizational climate is needed in order to create enthusiasm in achieving organizational performance. However, to achieve a good organizational climate is not easy, efforts are needed on how to unite organizational members as a solid work team and have the same motivation at work, the organizational climate will determine whether someone can carry out duties and responsibilities and in organizational behavior, Good behavior of organizational members or often known as Organizational Citizenship Behavior (OCB) is very important to have because it will contribute positively to the quality of work and organizational performance.